The impact of forest fragmentation on effective population sizes, mating systems and genetic diversity of forest trees in Guanacaste province, Costa Rica: The role of remote sensing in monitoring tropical forest fragments in Costa Rica - Cornelius, J. (2002)
271 páginas, 53 figuras, 72 tablas, ref.